Impact of Hydrophobic, Hydrophilic, and Mucus-Binding Motifs on the Therapeutic Potential of Ceftazidime Analogs for Pulmonary Administration - Kyle D. Apley; Stephanie N. Johnson; Jian Qian; Indeewara Munasinghe; Jennifer R. Klaus; Srilaxmi M. Patel; Kathryn E. Woods; Samalee Banerjee; Josephine R. Chandler; Chamani Perera; Nathalie Baumlin; Matthias Salathe; et al. (Antibiotics, 2025)
Background/Objectives: The pulmonary administration of antibiotics can be advantageous in treating pulmonary infections by promoting high intrapulmonary drug concentrations with reduced systemic exposure. However, limited benefits have been observed for pulmonary administration versus other administration routes due to its rapid clearance from the lung. Here, the effects of structural modifications on the epithelial permeability and antibacterial potency of a third-generation cephalosporin were investigated to improve the understanding of drug properties that promote intrapulmonary retention and how they may impact efficacy. Methods: Ceftazidime was modified by attaching 18 hydrophobic, hydrophilic, and mucus-binding motifs to the carboxylic acid distant from the beta-lactam by amidation. Epithelial permeability was investigated by drug transport assays using human bronchial epithelial air–liquid interface cultures. Antibacterial potency was determined by microtiter MIC assays with B. pseudomallei, P. aeruginosa, E. coli, and S. aureus. Results: A 40–50% reduction in the transepithelial transport rate was exhibited by two PEGylated ceftazidime analogs (mPEG8- and PEG5-pyrimidin-2-amine-ceftazidime) and n-butyl-ceftazidime. An increase in the transport rate was exhibited by four analogs bearing small and hydrophobic or negatively charged motifs (n-heptane-, phenyl ethyl-, glutamic acid-, and 4-propylthiophenyl boronic acid-ceftazidime). The antibacterial potency was reduced by ≥10-fold for most ceftazidime analogs against B. pseudomallei, P. aeruginosa, and E. coli but was retained by seven ceftazidime analogs primarily bearing hydrophobic motifs against S. aureus. Conclusions: The covalent conjugation of PEGs with MW > 300 Da reduced the epithelial permeability of ceftazidime, but these modifications severely reduced antibacterial activity. To improve the pulmonary retention of antibiotics with low membrane permeability, this work suggests future molecular engineering studies to explore high-molecular-weight prodrug strategies.